Experimental Study on Factors Affecting Waterproof Failure of Shield Tail Sealing System - JIANG Peifeng (Chengshi guidao jiaotong yanjiu)
［Objective］ Shield tail seal failure is a high risk factor in shield construction process, and shield tail sealing performance seriously affects construction safety and construction schedule. At present, the waterproof mechanism of the shield tail seal system has not yet been clarified in relevant researches, so it is necessary to conduct targeted research on the factors affecting the failure of the shield tail seal system. ［Method］ Taking the shield tail sealing system as the research object, the test method and equipment for its waterproof failure test are independently designed. Waterproof failure characteristics of the shield tail sealing system and its important influencing factors are studied. ［Result & Conclusion］ When the waterproof function of shield tail sealing system fails, the grease near the seepage channel will emulsify; shield tail clearance, shield tail brush wire length and other parameters all have a significant impact on the waterproof failure of shield tail seal. To ensure the positive design waterproof pressure of 0.6 MPa, when the shield tail brush wire length is selected to be 175, 200, 275, and 300 mm, respectively, it is recommended that the upper limits of the shield tail clearance should not be greater than 30.0, 34.3, 37.6, and 48.8 mm, respectively; when the design shield tail clearance is 30, 40, 50 mm and above, it is recommended that the selected shield tail brush wire length is not less than 175, 275, 300 mm, respectively.